Neutrophilic Inflammation in Severe Persistent Asthma - JATAKANON, ANON; UASUF, CARINA; MAZIAK, WAZIM; LIM, SAM; CHUNG, KIAN FAN; BARNES, PETER J. (American journal of respiratory and critical care medicine, 1999)
Airway inflammation in severe asthma is not well characterized but may involve neutrophils. We have compared induced sputum profiles in patients with asthma of varying severity and normal control subjects. We have also measured exhaled nitric oxide (NO) as a noninvasive marker of inflammation. Asthma severity was based on clinical features before treatment and the minimum medication required to maintain asthma control at the time of sputum induction, and classified as (1) mild: treated with inhaled beta(2)-agonist occasionally (n = 23; FEV(1), 91%; peak expiratory flow (PEF) variability, 10.5%), (2) moderate: requiring medium dose inhaled steroids to maintain control (n = 16; FEV(1), 88%; PEF variability, 9.1%), and (3) severe: despite using inhaled and oral steroids (n = 16; FEV(1), 61%; PEF variability, 36.2%). The asthmatic patients were nonsmokers with evidence of airway hyperresponsiveness or reversible airway obstruction, and free of respiratory tract infection for at least 6 wk. Sputum revealed significantly increased neutrophil numbers in severe asthma (53.0 [38.4- 73.5]%, p < 0.05) compared with mild asthma (35.4 [29.8-46.1]%) and normal control subjects (27.7 [20.6-42.2]%). Interleukin-8 (IL-8) and neutrophil myeloperoxidase (MPO) levels were increased in asthmatic patients, with the highest levels in severe asthma. Eosinophil numbers were increased in both mild and severe asthma, but interleukin-5 (IL-5) levels were highest in mild asthma, whereas eosinophil cationic protein (ECP) levels were highest in severe asthma. Exhaled NO levels were highest in asthmatic untreated with corticosteroids, but there was no significant difference between asthmatics using corticosteroids (Groups 2 and 3), regardless of clinical asthma severity. This confirms the role of eosinophils in asthma but suggests a potential role of neutrophils in more severe asthma.